2014
DOI: 10.1038/mi.2014.30
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of vitamin D on NOD2- and TLR-induced cytokines in Crohn's disease

Abstract: Accumulating evidence implicates defective innate immunity in the pathogenesis of Crohn's disease (CD). Ineffectual NOD2 (nucleotide-binding oligomerization domain 2) is the most common susceptibility gene contributing to CD. Vitamin D (vD), a potent modulator of innate and adaptive immunity, induces NOD2 gene expression and its downstream function. We hypothesized that the hormonal form of vD (1,25D) could beneficially modulate innate immune function in CD. Using peripheral mononuclear cells and monocyte-deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 49 publications
0
15
0
1
Order By: Relevance
“…Many studies have shown that numerous risk genes of CD code for molecules involved in host defense against pathogens, such as nucleotide-binding oligomerization domain 2 ( NOD2 ), ATG16L1 , and those implicated in the T helper type 17 (Th17) pathway[ 38 - 43 ]. Here, we tested the hypothesis that PBMCs of patients with CD, even at the stage of clinical remission, exhibit an altered gene expression profile upon challenge with pathogen-associated molecular patterns (PAMPs) and/or the immunomodulatory hormone vitamin D, which has previously been shown to exert differential effects on the expression of NOD2- and TLR-induced cytokines in the context of CD[ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that numerous risk genes of CD code for molecules involved in host defense against pathogens, such as nucleotide-binding oligomerization domain 2 ( NOD2 ), ATG16L1 , and those implicated in the T helper type 17 (Th17) pathway[ 38 - 43 ]. Here, we tested the hypothesis that PBMCs of patients with CD, even at the stage of clinical remission, exhibit an altered gene expression profile upon challenge with pathogen-associated molecular patterns (PAMPs) and/or the immunomodulatory hormone vitamin D, which has previously been shown to exert differential effects on the expression of NOD2- and TLR-induced cytokines in the context of CD[ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Underscoring its role in the pathogenesis of CD, vitamin D was shown to be an inductor of NOD2 gene expression[ 25 ]. Using peripheral blood mononuclear cells (PBMCs) and dendritic cells, Dionne et al[ 26 ] showed that 1, 25-vitamin D acts as a modulator of the innate immune system. However, little is known about the effects of vitamin D and the presence of NOD2 mutations on different gene expression levels in CD.…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiology regarding how vitamin D deficiency affects anti‐TNF‐α response requires further clarification. Vitamin D has also been showed to induce expression of the nucleotide‐binding oligomerisation domain (NOD2) gene, a susceptibility gene associated with Crohn's disease, and has been suggested to be a potential immune modulator in vitro . However, further studies clarifying the interaction between vitamin D, NOD2 and disease course are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Sadeghi et al and Dickie et al ( 36 , 37 ) both reported that 1,25(OH)D 3 suppressed the expression of TLR proteins and mRNA in human monocytes in a time- and dose-dependent fashion in vitro and reduced the recognition of bacterial specific antigens through monocytes. Another recent study showed that it decreased TLR-induced cytokine production and enhanced cytokine levels in peripheral mononuclear cells and monocyte-derived dendritic cells from CD patients ( 38 ). Our data showed that treating TNBS-induced colitis with 1,25(OH)D 3 could reduce TLR9 expression in the rat colon.…”
Section: Discussionmentioning
confidence: 99%